(untitled) (Journal of Gender and Social Issues, 2016)
The paper elaborates how three leading English newspapers of Pakistan, i.e. Daily Dawn, Daily The News and Daily. The total number of news stories and editorials analyzed was 270, out of which there were 219 News Stories and 51 editorials. The News gave maximum coverage while Dawn gave the smallest space to the issue. The maximum number of stories were having slant „Unfavorable to Government?. The Frame used in the largest number of stories was „IDPs as Co-Citizens?, the second „Taliban as Foe?, third „War on Terror as an Issue?, fourth „IDPs as Burden?, fifth „War on Terror as Solution? and the Frame found in minimum number of stories was „Taliban as Friend?. It is also important to note that coverage was more favorable towards IDPs, as the frame „IDPs as Co-Citizens? was used in a total of 117 stories.